Beryllium Mineralogy and Its Strategic Applications in Modern Industries - Sunidhi Rajput (International Journal of Minerals, 2024)
Beryllium, a rare lithophile element, exhibits unique physical and chemical properties that make it indispensable in various high-technology industries, including aerospace, nuclear energy, defense, and telecommunications. This review explores the mineralogy, extraction, applications, and resource distribution of beryllium, highlighting the metallurgical and industrial significance of its primary minerals, beryl and bertrandite. Despite being one of the lightest metals, beryllium boasts high strength, heat resistance, and conductivity, properties that support its strategic role in modern technological advancements. The review also addresses the challenges of beryllium mining, including the scarcity of high-grade ores and toxicity concerns, while considering global trends in resource concentration and new mineral discoveries. This discussion emphasizes the potential of innovative extraction and recycling methods to enhance beryllium supply and mitigate environmental impacts, thereby contributing to sustainable development in resource-dependent sectors.
Keywords: Beryllium; chemical metallurgy; mineralogy; nuclear industry; ore minerals; volcanic deposits